Impacts of Hall and ion slip Currents with Cattaneo -- Christov Features on the Peristaltic Blood Flow of Sisko Micropolar Nanofluid inside an Annulus through a Porous Medium - Mohamed, Yasmeen M.; El-Dabe, Nabil T. M.; Abou-Zeid, Mohamed Y.; Oauf, Doaa R. Mostapha and Mahmoud E. (Journal of Applied Nonlinear Dynamics, 2026)
The present analytical study exposed the impact of Cattaneo -- Christov heat and mass fluxes on the peristaltic blood influx. The impacts of Hall and ion slip currents are imposed. The Sisko micropolar nanofluid through porous midst is also presumed. The influences of heat generation absorption, thermal radiation, and chemical reaction are presupposed. The slip constraint for both velocity and temperature are postulated. The convective restrictions for nanofluid volume fraction and concentration are examined. The coupled differential systems of equations yield Soret and Dufour feature. The supposition of the long wavelength as well as low Reynolds number is applied to convert the system of partial differential equations into an unpretentious formula (ordinary differential ones). Over and above, the resultant analytical solutions of these equations are tackled essentially by employing both procedures of the conventional perturbation and the homotopy perturbation method (HPM). The diverse physical variables impact on the resultant allocations are calculated numerically and elucidated graphically through a group of graphs. It is recorded that the axial velocity dwindles with an escalating in the magnitudes of Hartman number. Meanwhile, it elevates with rising in Sisko parameter. The spin velocity decays with the elevating in the microrotation parameter. The enriching in heat relaxation causes a dwindling influence on the temperature. Further, escalating the nano Biot number causes a declination in nanoparticles volume fraction. This study is very helpful and has prosperous significant in diverse medical implementations as gold nanoparticles are utilized in the remedy of cancer tumor.